PROCESADO DE LABORATORIO PARA LA OBTENCIÓN DE LOS PARAMETROS CARACTERISTICOS DEL CORCHO EN PLANCHA - González, F; GONZÁLEZ, J R; de la Vega, R; Cristóbal, A (III Congreso Forestal Español, 2001)
We enumerate a register of trials and laboratory operations to process pluggings from probes and cork planks in general. We also set the cheracteristic parameter before and after heating and the formula to calculate them is shown
Keywords: Characteristic parameter; Cork; Quality